2023
DOI: 10.1051/0004-6361/202245085
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the early mass ejection in jet-driven protostellar outflows: Lessons from Cep E

Abstract: Context. Protostellar jets and outflows are an important agent of star formation as they carry away a fraction of momentum and energy, which is needed for gravitational collapse and protostellar mass accretion to occur. Aims. Our goal is to provide constraints on the dynamics of the inner protostellar environment from the study of the outflow-jet propagation away from the launch region. Methods. We have used the axisymmetric chemo-hydrodynamical code WALKIMYA-2D to numerically model and reproduce the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In most cavities traced by the continuum, we do not find enhanced emission along the cavity wall in the S(11) line, as would be expected for shocks owing to a wide-angle wind colliding with the cavity walls. Instead, we often find narrow shells of H 2 that appear similar to the bow shocks and wakes created by internal working surfaces within jets (Tafalla et al 2017;Tabone et al 2018;Rabenanahary et al 2022;Rivera-Ortiz et al 2023). The coincidence of the apex of the IRAS 16253 shell with the [Fe II]/Brα knot supports this picture.…”
Section: Scattered Light Cavities and H 2 Shellsmentioning
confidence: 67%
See 2 more Smart Citations
“…In most cavities traced by the continuum, we do not find enhanced emission along the cavity wall in the S(11) line, as would be expected for shocks owing to a wide-angle wind colliding with the cavity walls. Instead, we often find narrow shells of H 2 that appear similar to the bow shocks and wakes created by internal working surfaces within jets (Tafalla et al 2017;Tabone et al 2018;Rabenanahary et al 2022;Rivera-Ortiz et al 2023). The coincidence of the apex of the IRAS 16253 shell with the [Fe II]/Brα knot supports this picture.…”
Section: Scattered Light Cavities and H 2 Shellsmentioning
confidence: 67%
“…The knots trace shocks within the jets that likely originate in internal working surfaces, layers of shock-heated gas resulting from higher-velocity material colliding with slower-moving material in the jet (e.g., Schwartz 1983;Raga & Kofman 1992;Reipurth & Heathcote 1992;Suttner et al 1997;Völker et al 1999;Nisini et al 2002). Models and simulations invoking a jet with an oscillating velocity but a constant mass flow rate produce chains of such knots (Raga et al 1990;Raga & Kofman 1992;Rabenanahary et al 2022;Rivera-Ortiz et al 2023).…”
Section: Atomic Ionic and Molecular Knotsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical processes in the molecular outflow of core MM1#8 could be different from those of the intermediatemass Cepheus E core, which was recently studied with CO observations and numerical simulations (de Schutzer et al 2022;Rivera-Ortiz et al 2023). Rivera-Ortiz et al (2023) showed that one-velocity ejection variations successfully reproduce the observed features, especially the bimodal distribution of the dynamical timescales of the knots. On the contrary, we showed in this work that a two-velocity ejection mode is necessary to reproduce the observed velocity variations among the knots.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Rabenanahary et al (2022) compared simulations of an outflow driven by a pulsed jet and observations in CARMA-7 by Plunkett et al (2015). Rivera-Ortiz et al (2023) carried out simulations of a jet aimed at reproducing the Cepheus E outflow observed by de Schutzer et al (2022).…”
Section: Introductionmentioning
confidence: 99%